2022
DOI: 10.3389/fgene.2022.704988
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of a Novel Metastasis-Related lncRNA Prognostic Signature for Colorectal Cancer

Abstract: Background: Cancer metastasis-related chemoresistance and tumour progression are the leading causes of death among CRC patients. Therefore, it is urgent to identify reliable novel biomarkers for predicting the metastasis of CRC.Methods: The gene expression and corresponding clinical data of CRC patients were downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. Univariate and multivariate analyses were performed to identify prognostic metastasis-related lncRNAs. Nomograms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…NIFK-AS1 was found to potentially participate in dilated cardiomyopathy (DCM) through ceRNA [ 36 ]. Tang et al found NIFK-AS has been included in the prognostic signature to predict the prognosis of colorectal cancer(CRC) patients [ 37 ]. All these results indicate that NIFK-AS1 is a novel therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…NIFK-AS1 was found to potentially participate in dilated cardiomyopathy (DCM) through ceRNA [ 36 ]. Tang et al found NIFK-AS has been included in the prognostic signature to predict the prognosis of colorectal cancer(CRC) patients [ 37 ]. All these results indicate that NIFK-AS1 is a novel therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of heterogeneity in the expression of MIR200CHG is highly consistent with our findings in GC. In addition, MIR200CHG has been reported to be a prognostic biomarker by serving as a protective factor 48 50 or risk factor 51 in bladder urothelial carcinoma 48 , lung adenocarcinoma 49 , melanoma 50 , and colorectal cancer 51 based on in silico analysis of public datasets. Therefore, the function of MIR200CHG may be cancer tissue-dependent, cancer subtype-dependent and impacted by other factors such as subcellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…Four lncRNAs (ARRDC1-AS1, OIP5-AS1, BOLA3-AS1, and NIFK-AS1) were mentioned in previous COAD studies. 59 62 Collectively, these factors may lead to the further exploration of COAD progression and can be investigated as biomarkers and therapeutic targets for COAD.…”
Section: Discussionmentioning
confidence: 99%